A history of the Osage people - Burns, Louis F. (University of Alabama Press, 2004)
Traces 400 years of Osage culture from prehistoric times to the group's current status as an officially recognized tribe. Osage traditional lands are located in mid continental America encompassed by the present-day states of Arkansas, Missouri, Kansas, and Oklahoma. Major waterways through these lands and the defensible terrain of the Ozark range provided the tribe a distinct advantage in prehistoric and early historic times. A warlike people, the Osage long encroached on neighboring tribal lands, especially those of the Caddo to the southwest. Yet good natural boundaries and centuries of suc.